The Giver : a corpus-based analysis of word frequencies - Brandenburg-Weeks, Tara; Mohammed Abalkheel, Albatool (Penerbit Universiti Kebangsaan Malaysia, 2021)
Choosing appropriate reading material for language learners is not an easy task. It is necessary to keep in mind the specific purpose of the exercise and that the material chosen must support that purpose. Often, these goals will include developing fluency, increasing vocabulary knowledge, and increasing the rate at which vocabulary grows. One of the texts and novels commonly used for extensive reading in high intermediate level English as a Second Language coursework in the United States is The Giver, a young adult novel written by American author Lois Lowry. Due to its importance, we chose to analyze the novel within the framework of word frequency counts through the lens of the percent of words a learner must know in order to understand the particular text. A corpusbased method is utilized in the study to determine the types and frequency of vocabulary that The Giver provides. Common groupings of related low frequency lexical items and collocations are explored. This application of a corpus-based analysis of the text draws a picture of the vocabulary that is presented in The Giver, and how it matches 1K, 2K and AWL. The analysis reveals that 89.07% of the vocabulary was found to fall within these high frequency word lists, which gives the novel a somewhat higher comprehensibility than average academic texts. Analysis of low-frequency words reveals key vocabulary that increase comprehensibility when explicitly taught, as well as use of compound words, prefixes, and suffixes, that—if paired with instruction in vocabulary analysis techniques—can also increase the comprehensibility of the text. A conclusion is drawn regarding the appropriateness of this novel for the target audience in the specified course types, with suggestions for modifications and supplements for the text’s use within ESL/EFL classrooms.